Analysis of the Effect of Varying Concentrations of Strong Acids (HCl) and Weak Acids (CH3COOH) with Mixing of Bases (Detergent) on the Temperature Increase of the Reaction Results - Fahmi, Jam'an; Ramadhan, Dwi Sapri; Wardana, Dian; Safitri, Wulan Dwi; Zubir, Moondra; Siregar, Nurdin; Br Sebanyang, Resi Mai Linda Etaminta; Br Napitupuli, Monika Shinta Kasih; Lumbantoruan, Sifra H.R (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
Neutralization reactions between acids and bases are generally exothermic processes that release heat because of water formation from H⁺ and OH⁻ ions. This study aims to investigate the effect of varying concentrations of a strong acid (HCl) and a weak acid (CH₃COOH) on the temperature increase produced when these acids are reacted with a detergent-based alkaline material. Experiments were conducted using three acid concentrations—0.1 M, 0.3 M, and 0.5 M—each mixed with 3 g, 5 g, and 7 g of detergent in a reaction volume of 25 mL. The results indicate that increasing acid concentration correlates positively with greater temperature elevation. The largest temperature increase, 5.7°C, was observed in the reaction between 0.5 M HCl and 7 g of detergent, whereas the lowest increase, 0.5°C, occurred in the reaction between 0.1 M CH₃COOH and 3 g of detergent. Differences in ionization strength between strong and weak acids significantly influence the amount of heat released during neutralization. These findings demonstrate that both acid strength and base mass play important roles in determining the exothermic energy output of acid–base reactions.